BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PREEKLAMPSIA PADA IBU HAMIL - Rahakbauw, Grenny Zovianny; Pratama Putra, Bayu; Mustary, Musliha; Yulianita, Yulianita; Wahidah, Nurul Jannatul (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
WHO estimates that preeclampsia cases are seven times higher in developing countries than in developed countries. The cause of preeclampsia is not only caused by one factor, but many factors cause preeclampsia and eclampsia disease (multiple causation). Parity, history of hypertension, diabetes. Based on the survey results at Sansani Hospital, it is known to have an incidence of preeclampsia of 21.95%. The purpose of the study was to determine several factors that cause the incidence of preeclampsia. This type of research uses quantitative with a cross sectional approach. The research was conducted in January 2023 using simple random sampling. The sample amounted to 79 people. The results showed there was a relationship between parity (p value 0.000) and hypertension (p value 0.000) on the incidence of preeclampsia. Based on the results of the study is expected to be input and information to pregnant women regarding parity and history of the incidence of preeclampsia in pregnant women. For health workers, it is expected to be information in health services in order to prevent risk factors for preeclampsia in pregnant women as early as possible. Keywords: Hypertension, Parity, Preeclampsia